On the problem of protection of personal information (Journal of actual problems of jurisprudence, 2015)
The article analyzes the concepts and different regulatory approaches to the concept and content of personal information. It accentuates the de ficiencies of modern legislation on the status of personal information and their constituents. The article provides examples from practice confirming the existence of serious problems in the field of security of personal infor mation. It also suggests actionson how to improve the domestic legislation.